Cytoskeletal reorganization of human platelets induced by the protein phosphatase 1/2 A inhibitors okadaic acid and calyculin A. - Yano, Y (1995)
Okadaic acid (OA) and calyculin A (CLA), which are potent and specific inhibitors of serine/threonine protein phosphatases type 1 and 2A, have been shown to induce drastic changes in platelet morphology. The aim of this study was to analyse the molecular mechanisms of OA- or CLA-induced cytoskeletal reorganization, with a specific focus on microtubules and actin filaments. Confocal fluorescence microscopy revealed that OA or CLA altered the distribution of microtubules from marginal band arrangements to homogeneous patterns, consistent with the transmission-electron-microscopic finding that microtubules were fragmented and redistributed into pseudopod-like processes. In thrombin-activated platelets, OA or CLA induced extremely long pseudopods containing an array of microtubules and actin filaments, and a condensed mass of actin filaments in the centre of platelets. OA or CLA induced the constriction of actin filaments without an increase in filamentous (F)-actin, and also rather significantly inhibited actin polymerization in thrombin-activated platelets. Furthermore, neither OA or CLA enhanced phosphorylation of myosin light chain (MLC). By immunoprecipitation of platelet lysate with anti-alpha-tubulin antibody, a 90 kDa protein was co-precipitated with tubulin and was predominantly phosphorylated in the presence of OA. As the time-dependent phosphorylation of 90 kDa protein correlated well with the reorganization of microtubules, these data suggest that phosphorylation and dephosphorylation of this protein might play a role in the regulation of microtubule organization. These findings indicate that OA or CLA induces reorganization of microtubules and actin filaments via the phosphorylation of a microtubule-associated 90 kDa protein and an MLC-phosphorylation-independent mechanism. mechanism.